PENDIDIKAN KARATER SISWA DENGAN ENSAMBEL MUSIK DALAM KEGIATAN PENGEMBANGAN DIRI DI SMP NEGERI 3 PAYAKUMBUH - Kartika Afrina Roesli M.Y; Esy Maestro; Yos Sudarman (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the character building through self development activity at SMP N 3 Payakumbuh. The focus of the research was ensamble music activity, by adding character building in it. The research was conducted using qualitative type. The object of this research was the students of SMP Negeri 3 Payakumbuh. The research instrument was the researcher itself and assisted by stationery and photo cameras. The techniques of data collection were observation, documentation and interviews. Then, the technique of data analysis was done by gathering the data, describing the data and conclude the data. The results showed character building were carried out with application of the discipline and responsible values which are addressed to teachers and students who follow the activities of self- development ensamble music. Keywords: Character Education, Student, Ensambel Music, Self Development